Letter to the Editor. Urticaria in the Emergency Room: Recommendations for Diagnostic and Therapeutic Approach - Costa, Célia; Gonçalo, Margarida; GPEU – Grupo Português de Estudos de Urticária, Em nome do (Acta Médica Portuguesa, 2017)
N/a.